The fateful lightning [compact disc, unabridged] : a novel of the Civil War - Shaara, Jeff, 1952- (Shaara, Jeff, 1952- Civil War series, 2015)
In the concluding novel of his epic Civil War tetralogy, the dramatic story of the final eight months of battle from multiple perspectives: the commanders in their tents making plans for total victory, as well as the ordinary foot soldiers and cavalrymen who carried out their orders until the last alarum sounded. Through Sherman's eyes, listeners gain insight into the mind of the general who vowed to 'make Georgia howl' until it surrendered.